2020
DOI: 10.1021/acsami.0c01815
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Porous Aluminophosphate-Treated Wood for High-Efficiency Solar Steam Generation

Abstract: Solar steam generation as a promising solar energy conversion technology has attracted considerable interest in achieving seawater desalination and water purification. Although wood with fast water transportation and excellent heat localization has drawn particular interest in regard to its application for solar steam generation, challenges still remain in terms of its complicated processing techniques and relatively low efficiency. Here, we propose a facile, cost-efficient, and scalable brushing method to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 53 publications
1
42
0
Order By: Relevance
“…Recent research on generating solar steam has focused primarily on exploring photothermal materials with high absorption in the solar spectrum. Many researchers have investigated plasmonic absorbers [29] and noble metallic and nonmetallic nanoparticles such as NiO nanoparticles, [30] MoS 2 nanosheets, [31][32][33][34] processed wood, [35][36][37] activated carbon, [38,39] carbon nanotube, [40][41][42] carbon black, [43][44][45] carbon foam, [43,[45][46][47] carbon fiber, [48][49][50] graphene and graphene oxide, [39,[51][52] Au nanoparticles [53][54][55][56][57] on finding efficient photothermal conversion materials for the top layer to absorb the incident solar irradiation and convert it into heat energy. Many research groups [58][59][60][61] demonstrated the use of 3D porous graphene/carbon hybrid aerogels as photothermal material and achieved significantly higher photothermal efficiency under 1 sun (1 sun = 1 kW m −2 ) illumination.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on generating solar steam has focused primarily on exploring photothermal materials with high absorption in the solar spectrum. Many researchers have investigated plasmonic absorbers [29] and noble metallic and nonmetallic nanoparticles such as NiO nanoparticles, [30] MoS 2 nanosheets, [31][32][33][34] processed wood, [35][36][37] activated carbon, [38,39] carbon nanotube, [40][41][42] carbon black, [43][44][45] carbon foam, [43,[45][46][47] carbon fiber, [48][49][50] graphene and graphene oxide, [39,[51][52] Au nanoparticles [53][54][55][56][57] on finding efficient photothermal conversion materials for the top layer to absorb the incident solar irradiation and convert it into heat energy. Many research groups [58][59][60][61] demonstrated the use of 3D porous graphene/carbon hybrid aerogels as photothermal material and achieved significantly higher photothermal efficiency under 1 sun (1 sun = 1 kW m −2 ) illumination.…”
Section: Introductionmentioning
confidence: 99%
“…The X‐ray diffraction (XRD) of C‐L‐wood in Figure S9 in the Supporting Information shows strong cellulose peak. Benefiting from Fe 3+ catalytic pyrolysis property, this carbonize process featured significantly lower energy and cost consumption than most other biomass carbon‐based solar absorbers reported previously [ 34,47–49 ] (Figure 2g).…”
Section: Resultsmentioning
confidence: 85%
“…Li and coworkers [ 69 ] modified logs with arginine‐doped polydopamine (APDA) coating to obtain a double‐layer structure of wood‐based SSGDs; the efficiency of SSG was about 77.0% under 1 sun irradiation, and the desalination ability was still very stable after 100 cycles of the seawater evaporation process. Zhang and coworkers [ 70 ] took sodium chloride as the delignification agent to remove lignin from the wood and then coated FeCl 3 /PVA (polyvinyl alcohol) suspension on the wood substrate to obtain the double‐layer structure wood SSGDs (Fe–D‐wood) with superhydrophilic (delignification) at the bottom and hydrophobic (Fe 3 O 4 ) at the top; the evaporation rate of this SSGD was 1.30 kg m −2 h −1 and the conversion rate was 73.0%.…”
Section: Solar Steam Generator Based On Natural Productsmentioning
confidence: 99%